2015
DOI: 10.1001/jamapediatrics.2015.1631
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Transient Newborn Hypoglycemia and Fourth-Grade Achievement Test Proficiency

Abstract: IMPORTANCE Prolonged neonatal hypoglycemia is associated with poor long-term neurocognitive function. However, little is known about an association between early transient newborn hypoglycemia and academic achievement.OBJECTIVE To determine if early (within the first 3 hours of life) transient hypoglycemia (a single initial low glucose concentration, followed by a second value above a cutoff) is associated with subsequent poor academic performance. DESIGN, SETTING, AND PARTICIPANTSA retrospective population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
187
5
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 31 publications
4
187
5
6
Order By: Relevance
“…This was not the case, with infants with hypoglycemia having similar academic and cognitive outcomes and less problem behaviors as those without hypoglycemia. This finding is in contrast to the historic report by Lucas et al 2 and a recent report by Kaiser et al 9 Our results are similar to those of Tin et al 5 and McKinlay et al, 10 who found no significant differences in neurodevelopment of infants with neonatal hypoglycemia.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This was not the case, with infants with hypoglycemia having similar academic and cognitive outcomes and less problem behaviors as those without hypoglycemia. This finding is in contrast to the historic report by Lucas et al 2 and a recent report by Kaiser et al 9 Our results are similar to those of Tin et al 5 and McKinlay et al, 10 who found no significant differences in neurodevelopment of infants with neonatal hypoglycemia.…”
Section: Discussionsupporting
confidence: 71%
“…More recent studies show conflicting data on long-term developmental outcomes in both term and preterm-born children with neonatal hypoglycemia. 9,10 Several studies have examined the actual level and/or duration of hypoglycemia that is harmful to the infant brain, with inconclusive findings. However, existing reviews generally conclude that welldesigned studies are scarce and more research is needed.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be one of the several explanations [12,1618] why low and hypoglycaemia are common in children in sub-Saharan African hospitals [1,12]. The potential long-term neurological outcomes following hypoglycaemia in acute paediatric illness as described in neonates [19,20] have not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no particular cut off value of blood glucose concentration or hypoglycemic episode duration at which one can expect longterm complications. Despite almost all neonates that experience a transient asymptomatic low blood glucose up to 30 mg/dl in the first few hours of their lives as a normal adaptation to postnatal life, a recent study indicated that there is a relation between transient neonatal hypoglycemia (in the first three hours of life) and poor academic achievement at 10 years old of age [48]. Further studies in this regard are warranted to assess the generalizability of this conclusion -which represents an essential step before endorsing a universal newborn blood glucose screening program.…”
mentioning
confidence: 99%